MEMBANGUN KEPUTUSAN PEMBELIAN PELANGGAN COFFEE SHOP MELALUI BRAND IMAGE DAN BRAND TRUST: PERAN MEDIASI MINAT BELI - Muhammad arif; Salman Al-Farisi; Arief Ardiansyah Harahap (CERED Indonesia Institute, 2026)
The phenomenon faced by Cold and Brew Coffee Shop located at Jl. Abdullah Lubis No.77, Medan City, is a significant decline in the number of visitors and revenue over the past two months. This study aims to analyze the influence of Brand Image and Brand Trust on purchasing decisions through Purchase Intention as an intervening variable. The research method used is quantitative with an associative approach, involving 96 respondents who are customers of Cold and Brew Coffee Shop. Data was collected through questionnaires and analyzed using the SEM-PLS method. The results show that Brand Image significantly influences Purchase Intention (? = 0.651, p < 0.05) and Brand Trust also significantly influences Purchase Intention (? = 0.421, p < 0.05). Furthermore, Purchase Intention has a positive and significant effect on Purchase Decisions (? = 0.713, p < 0.05). However, Brand Image does not have a significant direct effect on Purchase Decisions (? = 0.258, p > 0.05), while Brand Trust has a significant effect on Purchase Decisions (? = 0.488, p < 0.05). This study confirms that Purchase Intention acts as an intervening variable that strengthens the influence of Brand Image and Brand Trust on Purchase Decisions